Contribution to the knowledge of diversity of Fusarium associated with maize in Malaysia - Mohd Zainudin, Nur Ain Izzati; Abd. Razak, Azmi; Mohamed Sidique, Siti Nordahliawate; Johari, Norazlina (Czech Academy of Agricultural Sciences, 2011)
The Fusarium species associated with maize are widely distributed in Malaysia. Eight Fusarium species were obtained in this country. A series of field samplings was conducted from 2006 to 2008, when 167 Fusarium isolates were obtained from maize plants in seven locations throughout Malaysia. The determination was based on micro- and macromorphological features (growth rates, colony features, mode of production of microconidia, macroconidia, conidiophores, and chlamydospores). F. proliferatum (29.9% isolates), F. semitectum (22.2% isolates), F. verticillioides (13.7% isolates), and F. subglutinans (12.6% isolates) were found out most frequently. F. equiseti, F. pseudograminearum, F. oxysporum, and F. solani were also isolated. This is the first report on the occurrence of F. equiseti, F. pseudograminearum, and F. subglutinans associated with maize plants in Malaysia.